Curso de especialização em Proeja: ressignificando a formação continuada de professores da EJA - Santos, Vilma Santana dos (2018)
This study presents a research about the policy of the teachers’ training in the education of Young People and Adults (EJA) offered by the latu senso post-graduation course in the level of specialization in Professional Education Integrated to the Elementary one for Young People and Adults – specialization in Proeja, which took place in the network of schools of the Federal Institute of Education, Science and Technology. implemented by the Decree nº 5.840/2006. This is a pioneering policy in this educational field, developed by the Ministry of Education and Culture (MEC) through the Secretary of Professional Education and Technology (SETEC) in 2006.to consolidate actions of the National Integration Program for Young People and Adults (Proeja) instituted in 2005 by the Federal Government. The research examined the connection of the Specialization Course in Proeja with the professional practices of the teachers-students, egresses from the course, from their own perspective in relation to the challenging situations these professionals of EJA are used to facing in their daily life. To do that, the Specialization course in Proeja (CEP), at the Federal Institute of Education, Science and Technology in São Paulo – Campus São Paulo, was analyzed through a) documental mapping; b) questionnaire, applied to 20 (twenty) teachers-students graduated from 2007 to 2015 in CEP, that aimed at collecting data of the teachers- students of this course about the received education and its relation with their professional performance after the conclusion of the course; and (c) interview with the former coordinator of CEP at IFSPSP. The data collected were organized in summary tables of information and charts. The research had as basic support: (a) available bibliographic sources from scholars such as Arroyo, Andrade, Cury, Di Pierro, Haddad, Soares and Ribeiro; (b) authors related to the ongoing teachers’ education such as Canário, Barroso, Contreras, Giovanni, Malglaive, Marin and Nóvoa and (c) EJA and Proeja inherent documental sources: laws, decrees, decrees law, reports, administrative rules and resolutions. According to the protagonists of this study, the obtained findings confirm the existence of a connection between the theory delivered in CEP of IFSP-SP and the daily school practice of these teachers-students. The CEP at IFSP-SP enabled an unprecedented training model of EJA teachers in the city of São Paulo which in general and in different ways dignified EJA in the work places of the teachers – students. Besides that, the professional identity and the autonomy of the teachers-students, required to the development of their academic background, were mobilized